VASYL STEFANYK’S WRITINGS IN A FOREIGN INTERPRETATION - Khorob, Stepan (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The aim of this study is to reveal the peculiarities of functioning of translations of Vasyl Stefanyk’s novellas in other languages: both in the Slavic and in the Romance-Germanic world, elucidate a translatological toolkit in old and contemporary interpretations. The research methods lie in employing a philological method and linguistic principles, as well as the principles of reader-response criticism through the prism of comparative approaches and comparative-historical principles of analysing the foreign language material, created by translators on the basis of Vasyl Stefanyk’s novellas. The results of researching into the posed problem led to the discovery of quite different methodological strategies of the foreign interpretation of different periods of translations of Vasyl Stefanyk’s works, the delineation of the whole complex of issues connected with a fictional being of Vasyl Stefanyk’s translated novellas, for example, in Polish, Bulgarian, Czech, Russian or English, German, French, Spanish languages. It is proved that foreign translators, first of all, used Stefanyk’s word as a fictional unit and succeeded the cases where the translation of Stefanyk’s text was done not literally, but, first and foremost, adequately for the writer’s ideological-aesthetical conceivement. Having implemented Russian and English translations of Vasyl Stefanyk’s novellas for analyzing the posed problem, there are made the conclusions as to creative successes and failures of numerous translators of Vasyl Stefanyk’s novellas into these languages. The scientific novelty of the article lies in the fact that it actualizes an important problem of being of the Ukrainian author’s prose in other languages in different cultural-historical environments, in the lingual space of these or those literatures.